PENGARUH KONSUMSI DAUN SIRSAK TERHADAP TEKANAN DARAH PADA PENDERITA HIPERTENSI: SYSTEMATIC REVIEW - La Ode Alifariki (NHM PRESS, 2022)
Hypertension is the main cause of cardiovascular disease whose incidence continues to increase in the community which can have a serious impact to cause death or is often referred to as the silent killer. One of the non-pharmacological therapies is giving soursop leaf decoction. The purpose of this study was to determine the effect of giving soursop leaves on blood pressure in patients with hypertension. This study was limited from 2000 to 2022 and found 3 eligible articles sourced from the Google Scholar search engine with the keywords “soursop leaves, blood pressure AND hypertension. The results of the study reported that from 3 articles it was found that bay leaves were effective in lowering blood pressure in patients with hypertension.